2020
DOI: 10.3390/sports8120154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutrition Knowledge in Female Gaelic Games Players

Abstract: Improvements in nutrition knowledge have been associated with increased carbohydrate consumption and greater adherence to dietary recommendations among female athletes. In order to assess whether nutrition knowledge interventions in female Gaelic games players may be beneficial, it is necessary to first of all investigate current levels of nutrition knowledge in this population. Given that many demographic characteristics have been shown to influence nutrition knowledge, it is also important for these to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 50 publications
(110 reference statements)
7
27
1
Order By: Relevance
“…Athletes that demonstrated higher nutrition knowledge consume more fruit, vegetables and CHO rich foods than those with lower levels of nutrition knowledge [ 22 ]. Previous research has identified that both elite and sub-elite Gaelic football players demonstrated poor nutrition knowledge [ 23 , 24 , 25 ]. Similarly, elite female Gaelic games players and elite male hurlers demonstrated inadequate levels of nutrition knowledge [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Athletes that demonstrated higher nutrition knowledge consume more fruit, vegetables and CHO rich foods than those with lower levels of nutrition knowledge [ 22 ]. Previous research has identified that both elite and sub-elite Gaelic football players demonstrated poor nutrition knowledge [ 23 , 24 , 25 ]. Similarly, elite female Gaelic games players and elite male hurlers demonstrated inadequate levels of nutrition knowledge [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent attempts to examine the SNK of male [ 23 , 24 , 25 ] and female [ 26 ] Gaelic football players is addressing a gap in the body of knowledge. On the other hand, there are some methodological limitations within the previous studies that would warrant the current study as the logical continuation of the previous research.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, effectively preparing for subsequent training or competition necessitates the monitoring of Gaelic football players during the post-match recovery timeline. Such knowledge is vital for injury prevention and nutritional strategies, tactical player rotation and the optimal management and periodization of training loads [ 10 , 23 , 24 , 25 ]. Therefore, this research aims to investigate the changes in markers of fatigue and performance attenuation during and following competitive Gaelic football match-play.…”
Section: Introductionmentioning
confidence: 99%